A survey on quality in education with respect to students' aptitude / Anis Abul Hasan Ashari - Abul Hasan Ashari, Anis (Universiti Teknologi MARA Cawangan Pahang, 2002)
Previous studies have examined various factors affecting the overall academic performance of accounting students in the education literature. In relation to this, a study was carried out to determine the best predictor of students' high performance in their accounting programmes. A questionnaire was developed and distributed to five public universities in the Klang Valley area; Universiti Islam Antarabangsa Malaysia, Universiti Teknologi MARA, Universiti Malaya, Universiti Kebangsaan Malaysia and Universiti Putra Malaysia. A total of 235 responses were received but only 213 were usable. Questions focused on six variables; motivation, the learning environment, exposure, aptitude, effort in terms of studying approaches and other factors such as family support and extracurricular activities. The results show that aptitude significantly affects student performance as compared to the other five variables. Thus, supporting previous research that aptitude is a significant predictor of student performance. The findings will provide valuable information to both educators and accounting students. Therefore, the study should give educators an empirical basis as to how to improve student performance and a guide to students on how to achieve success in their studies.